(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
Back in the history, Paolo Soleriâ€™s Arcosanti shows fifty years of evolution, from meta-project to potential new town, then prototype or urban laboratory, and now â€“ almost four years after the death of its deus ex machina â€“ looking for an identity, challenged by the risk of being frozen, butÂ hoping to be adopted by an Institution able to confirm his role as a lab of research and training. Being in posterity, this evolution can be read looking at the dialectic between the Soleriâ€™s creative, exploratory and doubtful process, and the way to participate of co-dreamers and inhabitants. Finally a town, even if born on the idea of a single mind, it is an expression of many actors, and stands up to zeitgeist and genius loci. So the architectural body of Arcosanti continues to confirm and regenerate the urban model proposed by Soleri, while the man-made component of the city evolves ... Â